2018
DOI: 10.1021/acs.cgd.8b00557
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystals and a Salt of the Bioactive Flavonoid: Naringenin

Abstract: Cocrystallization studies on naringenin with 27 coformers led to the formation of five new solid forms: piperazinium salt and four cocrystals with the coformers flavone, 4-hydroxypyridine, anthranilamide, and 4,4′-bipyridine. Structural characterization revealed that the hydrogen-bonded head-to-tail dimer motif in naringenin is maintained only in the cocrystal with flavone. All four neutral cocrystals maintain the S(6) O–H···OC intramolecular hydrogen bond seen in naringenin with this carbonyl oxygen atom bif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…In addition, cocrystals of the flavonoids with 4,4′-bipyridine (BP), a structural analog of VDP, were also taken into account. It is reported that in the cocrystals of Nar·BP and Gen·BP, the molar ratio of BP to Nar or Gen is 1:1, which is consistent with those of Nar·VDP and Gen·VDP. Therefore, the heteromolecular hydrogen bonds and the API/CCF ratio can be successfully predicted.…”
Section: Resultssupporting
confidence: 72%
“…In addition, cocrystals of the flavonoids with 4,4′-bipyridine (BP), a structural analog of VDP, were also taken into account. It is reported that in the cocrystals of Nar·BP and Gen·BP, the molar ratio of BP to Nar or Gen is 1:1, which is consistent with those of Nar·VDP and Gen·VDP. Therefore, the heteromolecular hydrogen bonds and the API/CCF ratio can be successfully predicted.…”
Section: Resultssupporting
confidence: 72%
“…Co-crystals have been reported as multiple component crystals in which all components are solid under ambient conditions whilst in their pure form [ 35 ]. One report suggested the co-crystallization of naringenin with 27 co-formers, which led to the formation of a salt and four co-crystals [ 36 ]. Several new forms of quercetin in the form of solvates and co-crystals were synthesized [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salts and cocrystals are some of the well-known techniques to improve the physicochemical properties of pharmaceutical and bioactive compounds and can be used in the purification of APIs [18][19][20][21][22][23][24][25][26][27]. Larger pKa variations between the components (usually ∆pKa > 3.0) can lead to the formation of salts, and salts often show greater solubilities than the single individual components [6,28,29].…”
Section: Introductionmentioning
confidence: 99%